KONSERVASI SUMBERDAYA ALAM DI TAMAN NASIONAL GUNUNG MERAPI: ANALISIS EKOLOGI POLITIK - Elisabet Repelita Kuswijayanti; Arya Hadi Dharmawan; Hariadi Kartodihardjo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Gunung Merapi is one of the mountain ecosystem in the center of Java island. The ecosystem is located under the administration of Yogyakarta Special Province and Center of Java Province. Since May 4th, 2004, the ecosystem has been appointed as Gunung Merapi National Park under the decree of Minister of Forestry Number 134/2004. Polemic over the appointment has been emerged before the decree issued and still continuing after. This research has been conducted in 1) Ngargomulyo village, Dukun, Magelang, Center of Java Province, 2) Jurangjero sand mining area in Ngargosoka, Srumbung, Magelang, Center of Java Province and 3) Kaliurang tourism destination area in Hargobinangun, Pakem, Sleman, Yogyakarta Special Province on Juli 2005 and Juni-Juli 2006. This research aimed to 1) mapping natural resources right and access mechanism and 2) analyse conflict between Environmental Non-Government Organisations (ENGOs) and Government. Using political ecology analysis, the research shows that the appointment of Gunung Merapi National Park only benefiting them living in tourism destination and sand mining area, but giving uncertainty for them living in village as a farmer. The research also identified that the conflict between government and ENGOs is the conflict of conservation discourses. The strategy for the future development of Gunung Merapi National Park is suggested as follows: 1) government should understand the natural resource access mechanism which has been worked in the Merapi ecosystem and 2) government should work together with the grassroots organisation to implement policy in the field level and with the ENGOs to develop natural resources conservation discourses. Key words: national park, access, conflict, political ecology, conservation discourses